The influence of two thermophilic consortia on troilite (FeS) dissolution - Giaveno Filippa, Maria Alejandra (2011)
Dissolution of a natural troilite by thermophilic consortia collected from two hot springs placed in Copahue geothermal region (Neuquen - Argentina) and later enriched in specific media for sulphur-oxidisers is reported in this paper. The enrichment was carried out at a temperature (65 °C) far away from those measured in the original hot springs (40.5 °C and 87 °C) in order to analyse the flexibility of the consortia to keep viability under other temperature conditions. Different microscopic techniques (SEM, TEM, fluorescence microscopy) allowed the partial characterisation of the cultures used as inocula in the bioleaching experiments. Results show that, as other metal sulphides, troilite dissolution can be strongly catalysed by sulphur (and iron) wild oxidising microorganisms present in the consortia from Copahue hot springs. According to our results, the addition of sulphur increased the bioleaching rate although the troilite dissolution is not limited by such addition because sulphur is in situ generated by chemical oxidation. Iron solubilised from troilite was partially precipitated mainly as jarosite. An additional and interesting result of our studies indicates that natural consortia can have a wide thermal flexibility and there are some strains among them - especially archaeas from Sulfolobales genus - that are able to survive at temperatures far away from the ones registered in the place where they were collected. © 2010 Elsevier B.V.